2020
DOI: 10.1186/s12992-020-00567-2
|View full text |Cite
|
Sign up to set email alerts
|

Developing monitoring and evaluation tools for event-based surveillance: experience from Vietnam

Abstract: Background: In 2016-2017, Vietnam's Ministry of Health (MoH) implemented an event-based surveillance (EBS) pilot project in six provinces as part of Global Health Security Agenda (GHSA) efforts. This manuscript describes development and design of tools for monitoring and evaluation (M&E) of EBS in Vietnam. Methods: A strategic EBS framework was developed based on the EBS implementation pilot project's goals and objectives. The main process and outcome components were identified and included input, activities, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…This is potentially the cause of concern about the limited contribution of EBS to the general surveillance. Experience from the pilot project in Vietnam showed that presence of structured data and reports were valuable for the MOH to understand the function of the EBS program and the success and challenges of implementing EBS (20).…”
Section: Discussionmentioning
confidence: 99%
“…This is potentially the cause of concern about the limited contribution of EBS to the general surveillance. Experience from the pilot project in Vietnam showed that presence of structured data and reports were valuable for the MOH to understand the function of the EBS program and the success and challenges of implementing EBS (20).…”
Section: Discussionmentioning
confidence: 99%
“…44,45 Training on case detection, notification, investigation, data analysis, and response was deemed lacking in several countries including Lao PDR, Mongolia, Vietnam, and the Solomon Islands. 11,12,17,43,44,80 Implemented in Lao PDR, the global data analysis and use training program called Stop Transmission of Polio Immunization and Surveillance Data Specialists, enabled building capacity on the management, analysis, and use of immunization and VPD surveillance data among the workforce at the subnational levels. 41 In addition, trainings organized by the WHO WPRO have been progressively more integrated across VPDs, emphasizing cross-cutting competencies, namely immunization and VPD surveillance data management, analysis, and use for tailored action, as conducted in Vietnam and Lao PDR.…”
Section: Workforce Capacitymentioning
confidence: 99%
“…Evaluating an EBS system is challenging [2,3]. We previously evaluated EBS systems in Vietnam using mixed methods that included 1) a retrospective data collection table sent electronically to all districts to collect logbook time stamps for event notification and response, 2) questionnaires sent electronically to all levels with acceptability and sustainability related questions and 3) key informant interviews and focus group discussions through field visits [10,11,16]. Evaluations showed that the pilot EBS worked as an effective early warning system for Vietnam.…”
Section: National Pheocmentioning
confidence: 99%
“…Vietnam has four administrative health regions; each has a regional public health institute that is responsible for technical direction and supervision of surveillance and response to diseases and outbreaks in that region [10,11]. Within each region, provincial centers for disease control lead surveillance and response activities in their respective provinces; in turn, district health centers within provinces coordinate district-level public health activities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation